Studi Pemanfaatan Sampah Organik Sayuran Sawi (Brassica juncea L.) dan Limbah Rajungan (Portunus pelagicus) untuk Pembuatan Kompos Organik Cair - Kusmiadi, Riwan; Prasetyono, Eva (Universitas Bangka Belitung, 2015)
The purpose of this study is to investigate the utilization of organic waste of green mustard and crab waste as materials for producing liquid organic compost. This study was conducted in experiment station and laboratorium of Chemistry, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung in February 2014. The design of experiment used randomized block design with formulation ratio as treatment. The treatments consist of F1 (100% green mustard organic waste), F2 (75% green mustard organic waste + 25% crab waste), F3 (50% green mustard organic waste + 50% crab waste) and F4 (25% green mustard organic waste + 75% crab waste). The results showed that green mustard organic waste and crab waste could produce quality of liquid organic compost in accordance with the Indonesian National Standard (SNI 19-7030-2004). All formulations between green mustard organic waste and crab waste, including F3 (50% green mustard organic waste + 50% crab waste) produced liquid organic waste in accordance with the Indonesian National Standard (SNI 19- 7030 2004).